2006
DOI: 10.1080/07357900600814771
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vascular Endothelial Growth Factor (VEGF) and Interleukin-8 (IL-8) Levels in Small Cell Lung Cancer

Abstract: This study was conducted to determine the value of the angiogenic serum factors, vascular endothelial growth factor (VEGF) and interleukin-8 (IL-8), in patients with small cell lung cancer (SCLC). These serum angiogenic factors were measured of 34 SCLC patients on the before and after chemotherapy in comparison with 20 healthy controls using ELISA method. Serum levels of VEGF and IL-8 were significantly increased in SCLC patients compared with healthy controls (p < 0.001). No statistically significant relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 17 publications
4
29
0
4
Order By: Relevance
“…Guida and colleagues (46) have reported that IL8 was unrelated with prognoses in patients with metastatic melanoma, even though the group with the highest levels of IL8 presented the lowest median OS. Other groups have reported lack of association of IL8 and prognosis (34,(47)(48)(49). Complexity of IL8 functions, technical issues, and/or characteristics of the selected patient populations may explain such discrepancies.…”
Section: Discussionmentioning
confidence: 86%
“…Guida and colleagues (46) have reported that IL8 was unrelated with prognoses in patients with metastatic melanoma, even though the group with the highest levels of IL8 presented the lowest median OS. Other groups have reported lack of association of IL8 and prognosis (34,(47)(48)(49). Complexity of IL8 functions, technical issues, and/or characteristics of the selected patient populations may explain such discrepancies.…”
Section: Discussionmentioning
confidence: 86%
“…Human SCLC cells express functional VEGF receptor (VEGFR)-2, VEGFR-3 and platelet-derived growth factor receptor (PDGFR)-β [Tanno et al 2004;Ioannou et al 2009]. Patients with SCLC express increased levels of serum VEGF and high pretreatment levels of VEGF are associated with poor response to chemotherapy and reduced survival [Ustuner et al 2008;Tas et al 2006;Salven et al 1998;Zhan et al 2009]. In addition, stem cell factor and its receptor, KIT, are coexpressed in up to 70% of SCLC cell lines and clinical SCLC samples.…”
Section: Molecular Targeting Agentsmentioning
confidence: 99%
“…This clinical correlation has not been definitively studied in SCLC, due in part to difficulty in obtaining SCLC biopsy samples (reviewed in [37]). Although the prognostic value of serum VEGF levels in SCLC patients in unclear [38,39], the role of angiogenesis in tumor progression and the success of anti-angiogenic agents across various tumor types has prompted investigation of angiogenic targeting in SCLC.…”
Section: Angiogenesis: Targeting Tumor-associated Vascular Growthmentioning
confidence: 99%